MODEL DINAMIK PERTUMBUHAN BIOMASSA UDANG WINDU DENGAN FAKTOR MORTALITAS BERGANTUNG WAKTU - sulanjari, Sulanjari; sutimin, sutimin (MATEMATIKA, 2008)
In this paper will be discussed the growth model of shrimp biomass. Biomass is total weight from population. The growth model of shrimp biomass is influenced by the growth model of weight and of population. The growth model of weight, here will be governed and based on Von Bertalanffyâ€™s model. The growth model of number population based on the exponential model and it has been constructed by mortality formula. From the growth model of shrimp biomass will be predicted when accurate harvest time to know the optimal harvest product. Â